2021
DOI: 10.1007/s11739-021-02790-0
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic prescriptions in the context of suspected bacterial respiratory tract superinfections in the COVID-19 era: a retrospective quantitative analysis of antibiotic consumption and identification of antibiotic prescription drivers

Abstract: This study aims to quantify antibiotic consumption for suspected respiratory tract superinfections in COVID-19 patients, while investigating the associated drivers of antibiotic prescribing in light of the current signs of antibiotic overuse. Adult patients with a positive COVID-19 diagnosis admitted to a Belgian 721-bed university hospital were analyzed retrospectively (March 11th–May 4th, 2020), excluding short-term admissions (< 24 h). Antibiotic prescriptions were analyzed and quantified, using Defined Dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
12
1
6
Order By: Relevance
“…Research suggests that the number of DDD may also be associated with a decreased antibiotic susceptibility [24]. In our study, the reported antibiotic consumption for COVID-19 confirmed admissions (0.87 DDD/admission and 8.92 DDD/100 hospital bed days) was lower than in a previously performed retrospective study by this research group (3.6 DDD/admission and 31.5 DDD/100 hospital bed days) [35]. Importantly, antibiotic consumption in ICU patients was taken into account in the retrospective study whereas this was not the case in the current prospective study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Research suggests that the number of DDD may also be associated with a decreased antibiotic susceptibility [24]. In our study, the reported antibiotic consumption for COVID-19 confirmed admissions (0.87 DDD/admission and 8.92 DDD/100 hospital bed days) was lower than in a previously performed retrospective study by this research group (3.6 DDD/admission and 31.5 DDD/100 hospital bed days) [35]. Importantly, antibiotic consumption in ICU patients was taken into account in the retrospective study whereas this was not the case in the current prospective study.…”
Section: Discussioncontrasting
confidence: 67%
“…A metaanalysis by Langford et al (2021) reported an antibiotic prescription rate of 71% [7]. A comparable retrospective study observed a prescription rate of 59% for respiratory antibiotics in ward patients [35]. The reasons for lower antibiotic prescription rate observed in our study are multiple: the prospective design of the study, the successful functioning of the AST with close follow-up of antibiotic prescriptions and an inclusion period that succeeded the first COVID-19 wave.…”
Section: Discussionmentioning
confidence: 43%
“…In a study from Belgium, fever and a low SpO 2 /FiO 2 (single peripheral blood oxygen saturation/fraction of inspired oxygen) ratio at presentation, underlying lung disease, and longer hospital stays were reported as the factors associated with antibiotics prescription for possible respiratory superinfection in patients with COVID-19. 21 Another study reported that the most important reason motivating clinicians to initiate antibiotic therapy was the clinical presentation, followed by laboratory markers of inflammation and radiological findings. 3 Based on past experiences, clinicians often make unnecessary decisions to prescribe antibiotics for patients with severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…В 96% случаев назначения АБ госпитализированным пациентам с COVID-19 препарат назначался при поступлении или в течение первых 48 ч после госпитализации, однако есть указания на более поздний период назначения АБ -в среднем семь дней [14,17,30,35]. Обзор назначения антибиотиков в 15 больницах Шотландии показывает, что в 62,4% случаев лечение антибиотиками начинали в день поступления пациента [36].…”
Section: частота антибактериальной терапииunclassified
“…Интересно, что наличие сопутствующих заболеваний не показало своей значимости в отношении назначения АБ [9]. Ещё в одном исследовании были выявлены следующие факторы, ассоциированные с назначением АБ: ли-хорадка при поступлении (ОШ 2,97; 95% ДИ 1, 22), более низкое отношение SpO₂/FiO₂ при поступлении (ОШ 0,96; 95% ДИ 0,92-0,99), ранее существовавшее заболевание лёгких (ОШ 3,04; 95% ДИ 1,12-8,27) и повышение уровня нейтрофилов [35].…”
Section: частота антибактериальной терапииunclassified